Sistem Aplikasi Tryout Dan Ujian Online Sekolah Dasar Berbasis Android (Study Kasus SD Negeri 2 Wates Timur, Pringsewu) - Tira Anindya, Atifa; Muslihudin, Muhamad (JELTec (Journal of Learning Technology), 2024)
This study introduces an innovative Android-based tryout and online examination application specifically designed for elementary schools, with a case study at SDN 2 Wates Timur. Traditional learning and evaluation methods in schools still heavily rely on face-to-face interactions, often lacking the efficiency offered by digital solutions. The novelty of this research lies in the integration of mobile technology tailored to the needs of young learners, enabling digital access to assessments and enhancing the overall learning experience. Data were collected through observation, interviews, and literature studies, while the application was developed using the System Development Life Cycle (SDLC) approach. Testing utilized black box methods on various Android devices to ensure compatibility. The results demonstrate improved efficiency in exam administration, simplified score recording for teachers, and reduced cheating among students. This application not only supports digital transformation in elementary education but also offers a replicable model for other schools seeking to integrate technology into their evaluation processes.